RATIONALIZATION OF REPRODUCTION – PATH TOWARDS DEHUMANIZATION OF HUMANITY: POLITICAL, LEGAL, AND ETHICAL ASPECTS OF USING ARTIFICIAL INTELLIGENCE IN EMBRYO SELECTION - Stjepanović, Bogdana M (Srpska politička misao, 2026)
Artificial Intelligence is becoming an essential part of human life, and the creation of life is no exception. While using AI in biomedically assisted reproduction (BMAR) gives new hope to couples struggling with infertility, it also raises a difficult question: where are the ethical limits of letting a machine interfere with human conception? This paper argues that the growing “rationalization” of the reproductive process through AI selection is not just a technical upgrade, but a deeply political and complex issue. In this paper, we analyze the legal and ethical risks of this trend, specifically focusing on how the process of conception is becoming “dehumanized”. A major concern is that we are relying too much on algorithms that nobody truly understands. This “black box” nature of AI can easily undermine the autonomy of parents and the validity of their informed consent in one of the most private moments of their lives. The philosophical danger of treating human embryos as mere objects for selection, which directly threatens their inherent dignity, is also examined. With the goal of pointing out gaps in our current laws, the paper looks closely at the regulations in the Republic of Serbia. We find that existing legal solutions are not fully prepared for these new challenges. Finally, we propose new regulatory steps that would put the dignity of the embryo first. Through a prism of ethics and a warning against the loss of human empathy, this paper concludes that an uncritical use of AI in reproduction carries a serious risk of turning the act of creating a human being into a cold, mechanical procedure.
Keywords: artificial intelligence (AI); embryo selection; dehumanization; dignity of embryos; legal and ethical challenges; Republic of Serbia